(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article compares the narrative organization of The Thousand and One Nights and Giovanni Boccaccio’s Decameron through the categories of frame narrative, narrative situation, temporal design, embedded storytelling, plot circulation, and ethical function. The study does not assume a direct genetic dependence between the two works. Instead, it distinguishes documented transmission, probable mediation, and typological parallelism, thereby avoiding the common methodological error of treating similarity as proof of borrowing. A comparative-narratological analysis shows that both collections transform a situation of crisis into a productive storytelling order. In The Thousand and One Nights, Shahrazad’s narration postpones death and gradually re-educates sovereign power; in the Decameron, ten young Florentines answer the social disintegration caused by the plague by constructing a temporary community governed by time, rules, themes, and reciprocal listening. The two frames therefore perform more than a connective or decorative function: they determine how the embedded tales are interpreted. At the same time, their compositional logics differ. The Nights is based on potentially open-ended continuation, suspense, interruption, and hierarchical address, whereas the Decameron is based on a closed numerical architecture, rotating authority, thematic days, and collective evaluation.